2017
DOI: 10.5219/779
|View full text |Cite
|
Sign up to set email alerts
|

Welfare of the mealworm (Tenebrio molitor) breeding with regard to nutrition value and food safety

Abstract: Livestock welfare is an important condition for obtaining high-quality and safe food. According to the legislation edible insects are classified as livestock; and for this reason it is necessary to comply with the edible insect welfare conditions. This article focuses on selected welfare conditions for mealworm (Tenebrio molitor) breeding, with special focus on the fat content influenced by different breeding temperature (17 °C, 23 °C and 28 °C). Maximum fat content 24.56% was observed at 23 °C. To obtain maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 17 publications
(2 reference statements)
3
27
0
Order By: Relevance
“…Similarly, Ravzanaadii et al [46] reported a crude protein concentration of 46.4% and crude fat concentration of 32.7% when the larvae were reared on wheat bran and vegetables, whereas Busler [47] reported a higher protein concentration (53.8%), and lower fat concentration (20.0%). Adámková et al [21] conducted experiments at 17, 23, and 28 • C, and observed the maximum fat concentration at 23 • C in the last and penultimate instar stages. According to Kulma el al.…”
Section: Nutritional Value Of the Larvaementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ravzanaadii et al [46] reported a crude protein concentration of 46.4% and crude fat concentration of 32.7% when the larvae were reared on wheat bran and vegetables, whereas Busler [47] reported a higher protein concentration (53.8%), and lower fat concentration (20.0%). Adámková et al [21] conducted experiments at 17, 23, and 28 • C, and observed the maximum fat concentration at 23 • C in the last and penultimate instar stages. According to Kulma el al.…”
Section: Nutritional Value Of the Larvaementioning
confidence: 99%
“…However, the mortality rate of crickets fed minimally processed, municipal-scale food waste and diets composed largely of straw was >99% without reaching a harvestable size. Some studies have revealed that low-value diets may be effective even at temperatures lower than the optimal range [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Yellow mealworm ( Tenebrio molitor ), a member of the family Tenebrionidae, is one of the most promising insect species suitable for mass production because it is easy to breed and feed [7,14]. Mealworm larvae fed on plant by-product diets grow well [15] and have a short life cycle: the egg stage lasts 3 to 9 days, the larval stage lasts 26 to 76 days, and the pupal stage lasts 5 to 17 days [16]. Larvae of T. molitor are rich in protein and unsaturated fat, and processed T. molitor larvae meal has been tested as a replacement of FM in the diet of several aquatic species.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 2000 different edible insect species have been reported (Jongema, ); however, a limited number of edible insects appear to have been employed for studies on bioactive properties. There are many studies of the nutritional value of edible insects (Blásquez et al ., ; Rumpold & Schlüter, ; Adámková et al ., ), but the growing consumer awareness of diet–disease relationships suggests a need to study this area of insect consumption as well. A wide range of biofunctional components (e.g.…”
Section: Introductionmentioning
confidence: 99%